Nin1p, a regulatory subunit of the 26S proteasome, is necessary for activation of Cdc28p kinase of Saccharomyces cerevisiae. - Kominami, K (1995)
The nin1-1 mutant of Saccharomyces cerevisiae cannot perform the G1/S and G2/M transitions at restrictive temperatures. At such temperatures, nin1-1 strains fail to activate histone H1 kinase after release from alpha factor-imposed G1 block and after release from hydroxyurea-imposed S block. The nin1-1 mutation shows synthetic lethality with certain cdc28 mutant alleles such as cdc28-IN. Two lines of evidence indicate that Nin1p is a component of the 26S proteasome complex: (i) Nin1p, as well as the known component of the 26S proteasome, shifted to the 26S proteasome peak in the glycerol density gradient after preincubation of crude extract with ATP-Mg2+, and (ii) nin1-1 cells accumulated polyubiquitinated proteins under restrictive conditions. These results suggest that activation of Cdc28p kinase requires proteolysis. We have cloned a human cDNA encoding a regulatory subunit of the 26S proteasome, p31, which was found to be a homolog of Nin1p.